Maqasid Syariah in the Judge's Decision on the Divorce Case at the Amuntai Religious Court - Shofa, Lailatus (JOURNAL OF ISLAMIC AND LAW STUDIES, 2025)
Marriage in Islam is a sacred institution aimed at establishing a family life characterized by sakinah (tranquility), mawaddah (affection), and rahmah (compassion). However, not all marriages fulfill these ideals, and divorce often becomes the last resort, including divorce petitions initiated by the wife (cerai gugat). This study aims to analyze the legal considerations of judges in divorce petition cases at the Amuntai Religious Court using a Maqāṣid al-Sharī‘ah approach. This research employs a descriptive-qualitative method based on document analysis, specifically focusing on Decision No. 114/Pdt.G/2023/PA.Amt. The Maqāṣid al-Sharī‘ah framework applied includes five essential aspects: the protection of religion (ḥifẓ al-dīn), life (ḥifẓ al-nafs), intellect (ḥifẓ al-‘aql), lineage (ḥifẓ al-nasl), and wealth (ḥifẓ al-māl). The findings reveal that the judge prioritized principles of public interest (maṣlaḥah), particularly ḥifẓ al-nafs and ḥifẓ al-nasl, in addressing a marital relationship marked by verbal abuse, ambiguity regarding the status of divorce, and the protection of children's lineage from a marriage that was not renewed through a valid contract. Although the petitioner believed that a triple divorce (ṭalāq thalāth) had occurred, the judge ruled only a single bain sughra divorce due to the absence of formal legal evidence. This divergence highlights the judge’s prudence in avoiding greater harm (maḍarat). The study underscores that Maqāṣid al-Sharī‘ah can serve as an evaluative framework for resolving divorce petition cases in a manner that is just, contextual, and responsive to vulnerable parties-particularly women and children.